Political tensions in Iraqi television election debate programs and their impact on public participation in the 2025 parliamentary elections from an academic perspective (Journal of Imam Al-Kadhim College, 2026)
Election debate programs in the media have programmatic weight and priority in planning, implementation and technical treatment, through which those media, especially Iraqi satellite channels/the research sample, are keen to give them important time spaces and sometimes they are open in some media coverage.The researcher identified the research problem as the space of ambiguity created by election debate programs and their political tensions among specialists regarding the repercussions or effects of these television programs on the public who are aware of elections as a necessary democratic and political participation for 2025.The research adopted several objectives, including: identifying the type of cognitive, emotional, or behavioral repercussions that election debate programs and their political tensions translate into public decisions to participate in elections or not.Regarding the most prominent findings: Over 87% of academics in Baghdad believe that election debate programs prioritize political agendas over the public interest by supporting entities and candidates affiliated with the satellite channel owners. Meanwhile, 85% of them say they watch these programs because of the presenters' professional skills and their ability to manage the dialogues between the participating parties.
Keywords: Electoral Debate - Talk Shows - Media Political Tensions Academic Elite -Societal Implications; Electoral Debate; Talk Shows; Media Political Tensions; Societal Implication; Academic Elite s